Theory of Concentrated Vortices An Introduction - Alekseenko, S. V.; Kuibin, P.A; Okulov, V. L. (Springer Berlin Heidelberg : Imprint: Springer, 2007)
This book presents comprehensive and authoritative coverage of the wide field of concentrated vortices observed in nature and technique. The methods for research of their kinematics and dynamics are considered. Special attention is paid to the flows with helical symmetry. The authors have described models of vortex structures used for interpretation of experimental data which serve as a ground for development of theoretical and numerical approaches to vortex investigation. Achievements in the fields of stability analysis, waves on vortices and vortex breakdown are also presented.